2005
DOI: 10.1007/s11207-005-8776-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Variations in Solar Differential Rotation and Sunspot Activity

Abstract: The solar equatorial rotation rate, determined from sunspot group data during the period 1879-2004, decreased over the last century, whereas the level of activity has increased considerably. The latitude gradient term of the solar rotation shows a significant modulation of about 79 year, which is consistent with what is expected for the existence of the Gleissberg cycle. Our analysis indicates that the level of activity will remain almost the same as the present cycle during the next few solar cycles (i.e., du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…The B parameter was also found to have a small decreasing trend from about B = 2.7 to about B = 2.4, but the evolution of B was dominated by a roughly 80-year oscillation with an amplitude of ±0.3 deg/day. However, these results cannot be directly compared with the long-term evolution of the best-fit values of the two rotation parameters found in this study since Javaraiah et al (2005) did not separately consider the two hemispheres.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The B parameter was also found to have a small decreasing trend from about B = 2.7 to about B = 2.4, but the evolution of B was dominated by a roughly 80-year oscillation with an amplitude of ±0.3 deg/day. However, these results cannot be directly compared with the long-term evolution of the best-fit values of the two rotation parameters found in this study since Javaraiah et al (2005) did not separately consider the two hemispheres.…”
Section: Discussionmentioning
confidence: 78%
“…Earlier studies have already noted that the rotation parameters depict long-term trends and long-term oscillations (see, e.g., Makarov et al 1997;Kitchatinov et al 1999;Javaraiah et al 2005;Brajsa et al 2006, and references therein). For instance, Javaraiah et al (2005) found that the Ω 0 parameter depicts a fairly systematic decline during cycles 12 to 23 from roughly Ω 0 = 14.55 deg/day to Ω 0 = 14.45 deg/day, with some evidence of weak century-scale oscillation superimposed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This property of the solar activity, known as the Gleissberg cycle, is now well established (Zolotova and Ponyavin, 2014;Vázquez et al, 2016;Komitov et al, 2016). Some authors have suggested that the activity is currently at the minimum of the recent Gleissberg cycle (Javaraiah, Bertello, and Ulrich, 2005a;Zolotova and Ponyavin, 2014;Gao, 2016). In this article we attempt to predict the relative amplitudes of the solar cycles that correspond to the rising phase of the upcoming Gleissberg cycle.…”
Section: Introductionmentioning
confidence: 99%
“…For the investigation of possible variations in the solar rotation, the Greenwich data set was used by Balthasar & Wöhl (1980), Arévalo et al (1982), and Balthasar et al (1986); the Kanzelhöhe data set by Lustig (1983); the Mt. Wilson data set by Gilman & Howard (1984) and by Hathaway & Wilson (1990); the Mitaka data set by Kambry & Nishikawa (1990); the Suzuka data set by Suzuki (1998); the extended Greenwich data set by Pulkkinen & Tuominen (1998), Javaraiah (2003), Zuccarello & Zappalá (2003), Javaraiah et al (2005), Javaraiah & Ulrich (2006), and Brajša et al (2006Brajša et al ( , 2007; the Kodaikanal data set by Gupta et al (1999); and the Abastumani data set by Khutsishvili et al (2002). Also, temporal variations in the solar rotation were studied using other Article published by EDP Sciences A17, page 1 of 6…”
Section: Introductionmentioning
confidence: 99%